2014
DOI: 10.1007/s11746-014-2450-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Some Physicochemical Properties of Mixtures of Morama Seed Oil with (C6–C9) n‐Alkanes at 298.15 and Atmospheric Pressure

Abstract: Densities q, ultrasonic speeds u and dynamic viscosities g, of mixtures of morama, Tylosema esculentum, seed oil with n-hexane, n-heptane, n-octane and n-nonane were determined over the entire composition range at 298.15 K and atmospheric pressure. Excess molar volumes, V E m , excess molar free volumes V E f , deviations in isentropic compressibility, Dj s , deviations in ultrasonic speed, Du, deviations in viscosity, Dg, and the excess free energy of activation of viscous flow, DG* E , were calculated theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…The purity of the cosolvents was tested by comparing their densities, ρ , ultrasonic speed, u , and dynamic viscosities, η , at 298.15 K, with the reported literature data in Table , which also includes our measured values of these quantities. It was observed that the measured values of ρ , u , and η were in good agreement with the literature data (Aminabhavi et al, ; Aralaguppi et al, ; Gonzalez et al, , ; Yeboah et al, ). Ultra‐pure water used in the calibration of the interferometer and densimeter was obtained as described elsewhere (Yeboah et al, ).…”
Section: Methodssupporting
confidence: 88%
See 4 more Smart Citations
“…The purity of the cosolvents was tested by comparing their densities, ρ , ultrasonic speed, u , and dynamic viscosities, η , at 298.15 K, with the reported literature data in Table , which also includes our measured values of these quantities. It was observed that the measured values of ρ , u , and η were in good agreement with the literature data (Aminabhavi et al, ; Aralaguppi et al, ; Gonzalez et al, , ; Yeboah et al, ). Ultra‐pure water used in the calibration of the interferometer and densimeter was obtained as described elsewhere (Yeboah et al, ).…”
Section: Methodssupporting
confidence: 88%
“…It was observed that the measured values of ρ , u , and η were in good agreement with the literature data (Aminabhavi et al, ; Aralaguppi et al, ; Gonzalez et al, , ; Yeboah et al, ). Ultra‐pure water used in the calibration of the interferometer and densimeter was obtained as described elsewhere (Yeboah et al, ). All purified organic solvents were stored in brown glass bottles and fractionally distilled and ultrasonically degassed immediately before the preparation of binary mixtures.…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations